THE FOOD AS A HUMAN RIGHT AND RISK IN A COMPLEX SOCIETY (Revista Inclusiones, 2021)
This work aims to analyze the theme of food as a human right and risk in a complex society from theangle of the Study of Risk an Ecology of the Human Rights . Here, risk condensates a particularsymbiosis of future and society, allows the construct of communication and describes the chance ofreflecting about the future. It is based on two questions: the semantic load underlying the termssecurity, insecurity and risk; and how the food insecurity modality is present in contemporary society.The idea is that civilization has advanced trying to abolish the imminent perils of catastrophes, but itdid not find sustainability or a favorable balance to eliminate the complex social problems it produces.Thus, from the very decision structures risk is fomented. It concludes on the paradoxical aspect ofthis society, whose events operate on risk productions: the more food production, more food insecuritythe more communication and education, more disinformation; the more knowledge, more un-knowledge.